Edukasi Monopoli Anemia (GEMOMIA) pada Remaja Putri di SMAN 01 Kabupaten Muaro Jambi - Solihin, Sayuti; Triana, Winda (Jurnal Salam Sehat Masyarakat (JSSM), 2024)
Anemia is often found in young women, with a ten times greater risk of suffering from anemia in young men. The aim of this community service is to provide an understanding of the importance of preventing anemia in controlling stunting using the anemia monopoly educational game (GEMOMIA) for young women. There are several methods used when providing education, namely by lectures, discussions and interpretation. This service was carried out at SMA N 1 Muaro Jambi with a target number of 100 people. This service activity was carried out by 2 lecturers and 5 students. Understanding assessment is carried out through written tests before and after education. Activities are carried out with a pre-test stage, an education and discussion implementation stage and an evaluation stage with a post-test. PkM activities with pre-test scores obtained with a comparison mean score between pre-test and post-test was 1.48. There were also 73 (73%) respondents who increased their knowledge, 14 (14%) respondents who maintained their knowledge and 13 (13%) ) respondents whose knowledge decreased. The results of the bivariate analysis test with the Wilcoxon T-Test on pre-test and post-test respondents. The results of data testing show a p value = 0.000 < 0.05, so it can be concluded statistically that there is a significant difference in knowledge between knowledge before and after education. Educational media for Stunting Control through the Anemia Monopoly Educational Game for adolescent girls can increase the knowledge of adolescent girls.